Identification of Chemistry Learning Problems Viewed from Conceptual Change Model (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This study aimed at describing and explaining chemistry learning problems viewed from conceptual change model and misconceptions of students. The study was qualitative research of case study type conducted in one class of SMAN 1 Singaraja. Subjects of the study were a chemistry teacher and students. Data were obtained through classroom observation, interviews, and conception tests. The chemistry learning problems were grouped based on aspects of necessity, intelligibility, plausibility, and fruitfulness. Data were analyzed descriptively. The results of the study showed that the chemistry learning problems related to the aspect of necessity were that the teacher did not carry out the laboratory work and did not discuss the properties of the buffer solution. The problems related to aspects of intelligibility were the teacher asked successive questions, answered her own questions, gave wrong information, made unclear and wrong analogies, and did not ask student reasons. The problems related to the plausibility aspects were that the teacher had less emphasis on the importance of context and neglected the students’ alternative conceptions. The problems related to the fruitfulness aspects were that the teacher was less likely to provide complex problems especially with regard to the application of the buffer solution in everyday life. Students experienced misconceptions on some concepts of buffer solution.